Fibrinogen status in relapse and remission of childhood nephrotic syndrome - Veronica Lily Limantara; Ida Bagus Mudita; I Ketut Suarta (Indonesian Pediatric Society, 2006)
Objective To evaluate fibrinogen concentration of relapsing neph-rotic syndrome (NS) in children, and to investigate relationshipbetween fibrinogen with albumin and cholesterol.Methods A cross-sectional study among NS patients admitted topediatric outpatient clinic and pediatric ward at Sanglah Hospital,Denpasar, from November 1, 2003 to January 31, 2004. All pa-tients were evaluated for clinical and laboratory findings of relapseand remission, including edema, proteinuria, serum albumin, totalcholesterol, as well as total platelet count and fibrinogen concen-tration to evaluate coagulation parameters in nephrotic patients.Results There were 36 patients with the mean age of 7.4 (SD 2.3)years included in this study. Mean fibrinogen concentration in re-lapse state was 671.8 (SD 102.7) mg/dl, while in remission statewas 255.2 (SD 50.5 mg/dl); the mean difference was 416.6 mg/dl(95% CI 362.9;470.4; P<0.001). Fibrinogen was inversely andstrongly correlated with serum albumin concentrations (r=-0.91;P<0.001). Fibrinogen was positively and strongly correlated to to-tal cholesterol (r=0.80; P<0.001). Using multiple regression analy-sis, it was shown that only relapse/remission status was signifi-cantly associated with fibrinogen concentration (P<0.001).Conclusion Fibrinogen status is significantly correlated with re-lapse and remission status of NS in childhood patients.